2022
DOI: 10.3390/rs14246221
|View full text |Cite
|
Sign up to set email alerts
|

Precipitable Water Vapor and Fractional Clear Sky Statistics within the Big Telescope Alt-Azimuthal Region

Abstract: The development of a network of ground-based telescopes requires detailed astroclimatic studies. This paper presents the spatial distributions of precipitable water vapor (PWV), total cloud cover (TCC) and cloud base height (CBH). With the aim of a representative description of the precipitable water vapor, a method for correcting this characteristic which takes into account the underlying surface is proposed. The method uses the exponential decrease in the water vapor content with the altitude and is based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In addition, both Wang et al [14] and Yang et al [15] concluded that soil moisture plays a more dominant role in precipitation-use efficiency and evapotranspiration-precipitation coupling. Moreover, Shikhovtsev et al [16] utilized the fifth generation ECMWF (European Centre for Medium-range Weather Forecasts) atmospheric reanalysis (ERA5) precipitable water vapor (PWV) data within 2010-2020 to establish a functional relation between the PWV and the elevation, exhibiting that the decrease of PWV with the elevation was exponential with a height scale of 1000 m. The ERA5 product was also reported to overestimate the PWV values by 1-2 mm in the Big Telescope Alt-azimuthal region (40 [16].…”
Section: Highlights Of Research Articlesmentioning
confidence: 99%
“…In addition, both Wang et al [14] and Yang et al [15] concluded that soil moisture plays a more dominant role in precipitation-use efficiency and evapotranspiration-precipitation coupling. Moreover, Shikhovtsev et al [16] utilized the fifth generation ECMWF (European Centre for Medium-range Weather Forecasts) atmospheric reanalysis (ERA5) precipitable water vapor (PWV) data within 2010-2020 to establish a functional relation between the PWV and the elevation, exhibiting that the decrease of PWV with the elevation was exponential with a height scale of 1000 m. The ERA5 product was also reported to overestimate the PWV values by 1-2 mm in the Big Telescope Alt-azimuthal region (40 [16].…”
Section: Highlights Of Research Articlesmentioning
confidence: 99%
“…Investigations with various methods (e.g., [8,39,65,[70][71][72][73][74]) reveal other promising sites in Eurasia with better conditions in comparison with the Suffa plateau. In paper [8] based on the NASA GEOS-FPIT model, the Eastern Pamirs and Tibet are shown to be the best places.…”
Section: Comparison Of the Candidate Sites For Millimeter-wave Telesc...mentioning
confidence: 99%
“…Well-known areas with PWV conditions suitable for millimeter and sub-millimeter astronomy are the Chajnantor area in northern Chile, Dome A and Dome C in Antarctica, Mauna Kea in Hawaii, Summit Camp in Greenland, and Yangbajing in Tibet (Tremblin et al 2012). Hitherto, there is a continuous interest in determining new candidates for radio astronomy sites; thus new sites are constantly being evaluated in terms of PWV, such as the Qitai Telescope (QTT) in China (Li et al 2020) and the Big Telescope Alt-Azimuthal (BTA) region in Russia (Shikhovtsev et al 2022). Moreover, there is a high amount of interest in the inclusion of new telescopes in global-scale Very Large Baseline Interferometry (VLBI) networks, such as the Event Horizon Telescope (EHT).…”
Section: Introductionmentioning
confidence: 99%
“…Iserlohe et al (2021) compared data obtained from the Far Infrared Field-Imaging Line Spectrometer (FIFI-LS) of the Stratospheric Observatory for Infrared Astronomy (SOFIA), with PWV data extracted from the European Centre for Medium-Range Weather Forecasts (ECMWF). Shikhovtsev et al (2022) presented a method to evaluate the BTA region using PWV data from the ERA-5 reanalysis dataset. Kuo (2017) used MERRA-2 data to evaluate five sites of interest in millimeter-wave observations: South Pole and Dome A in Antarctica, Chajnantor in Atacama, Ali in Tibet, and Summit Camp in Greenland.…”
Section: Introductionmentioning
confidence: 99%